Mucosal and systemic immune responses in Senegalese sole (Solea senegalensis Kaup) bath challenged with Tenacibaculum maritimum: A time-course study. Issue 87 (April 2019) - Guardiola, F.A.; Mabrok, M.; Machado, M.; Azeredo, R.; Afonso, A.; Esteban, M.A.; Costas, B.
Abstract: Tenacibaculosis, caused by Tenacibaculum maritimum, continues to inflict substantial losses among cultured marine species, particularly in the Senegalese sole. However, the immune mechanisms in fish involved in fighting against this disease are still poorly understood. Thus, the present study aimed to investigate the skin mucus's terminal carbohydrate composition, several immune-related enzymes (i.e. lysozyme, peroxidase, proteases and antiproteases), the haemolytic activity of complement and the bactericidal activity in the skin mucus and plasma of the Senegalese sole in a time-course study following a bath challenge with T. maritimum . The haematological profile and the kinetics of cell migration post-infection were also considered. The bath challenge induced slight variations in the terminal carbohydrate composition of Senegalese sole skin mucus. In general, results from this study showed a delay in the mucosal immune response compared to that found at the systemic level (i.e. blood and plasma). For instance, a significant increase in the skin mucus's lysozyme, complement, protease and antiprotease activities were observed at the end of the experiment (14 d post-challenge). Interestingly, the higher activity of these enzymes could be related to the skin mucus's bactericidal capacity and haemolytic complement activity, suggesting that these enzymes play an important role in the defence against Gram-negative bacteria. The haematological profile revealed a significant increase in circulating neutrophils in challenged fish after 48 and 72 h, which was positively correlated to the increments observed in peroxidase and lysozyme activities, respectively, in the plasma of challenged fish at the same time. Although the route of entry and the survival strategy of T. maritimum are still not fully elucidated, results from the present study will contribute to this endeavour through the study of the mucosal immune responses of fish against this particular pathogen. Graphical abstract: Image 1 Highlights: Fish immune mechanisms involved in tenacibaculosis are still poorly understood. T. maritimum bath challenge not revealed great variations in the carbohydrates profile in fish skin mucus. A delay in the mucosal immune response was observed compared to that found at systemic level (plasma). Skin mucus had a stronger bactericidal activity than that from plasma against bacterial species tested. A general increase was observed in all immune parameters evaluated in skin mucus at the end of the trial.